Vibration-assisted coherent excitation energy transfer in a detuned dimer - 王信 陈浩 李晨宇 李宏荣 (Chinese physics B, 2017)
The important role of high-energy intramolecular vibrational modes for excitation energy transfer in the detuned photosynthetic systems is studied. Based on a basic dimer model which consists of two two-level systems （pigments） coupled to high-energy vibrational modes, we find that the high-energy intramolecular vibrational modes can enhance the energy transfer with new coherent transfer channels being opened when the phonon energy matches the detuning between the two pigments. As a result, the energy can be effectively transferred into the acceptor. The effective Hamiltonian is obtained to reveal the strong coherent energy exchange among the donor, the acceptor, and the high-energy intramolecular. A semi-classical explanation of the phonon-assisted mechanism is also shown.